Analysis of female windsurfers' performance using global positioning system information during competitions - Chun, S. B.; Park, J. C.; Park, S. H.; Kim, J. S. (Korean Journal of Sport Biomechanics, 2021)
Objective: This study aimed to identify the different wind speed categories and competitive level among windsurfers through GPS variables to provide the useful information on the development of training programs for enhancing windsurfers' performance. Method: Data from 69 female athletes who participated in 27 races during the 2018-2019 windsurfing season were used for the analysis. Average board speed, total race time, total distance, upwind race time, downwind race time, beam reach race time were collected through GPS. Unconfirmed data were excluded along with penalty point data. The wind conditions were classified as light, light to medium, medium, medium to heavy, and heavy wind, the competitive levels were classified as level 1, level 2, and level 3. Results: As for the average board speed, the level 1 or level 2 group showed higher board speed than the level 3 group in all wind conditions except for the light wind. The total race time and upwind race time showed less time in level 1 or level 2 group than level 3 group in all wind conditions. The total distance, downwind race time and beam reach race time showed less distance and time in level1 group than level 3 group under sufficient wind conditions. Conclusion: Our results show that the aerobic capacity to sustain pumping during upwind course in wind conditions below 15 kts effects performance. In wind conditions of 15 kts or more, indicated that the board control for the fast board speed and small distance required during up, down, beam reach courses had an effect on competition performance. This information can be provided to windsurfers and coaching as basic data for training programs to improve performance.